Characterization and expression profiling of NOD-like receptor C3 (NLRC3) in mucosal tissues of turbot (Scophthalmus maximus L.) following bacterial challenge. Issue 66 (July 2017) - Hou, Zhumei; Ye, Zhi; Zhang, Dongdong; Gao, Chengbin; Su, Baofeng; Song, Lin; Tan, Fenghua; Song, Huanhuan; Wang, Yu; Li, Chao
Abstract: The mucosal surfaces are important for teleost as they are directly and continuously exposed to pathogen-rich aquatic environments. Scrutinization and recognition of the attached pathogens is the first crucial step of mucosal immunity initiation. Nucleotide oligomerization domain (NOD)-like receptors (NLRs) are a large group of intracellular pathogen recognition receptors (PRRs) which play key roles in pathogen recognition and subsequent immune signaling pathways activation. In this study, we identified two NLRC3 genes (NLRC3a and NLRC3b), a subfamily of NLRs from turbot, and profiled their expression patterns in mucosal tissues following bacterial challenge. NLRC3a transcript contains an open reading frame (ORF) of 3405 bp that encodes a putative peptide of 1134 amino acids. While NLRC3b has an ORF of 3114 bp encoding 1037 amino acids. A caspase recruitment domain (CARD) at N-terminus characterized turbot NLRC3a, while NLRC3b seems to be unique to teleost, containing a fish specific NACHT associated (FISNA) domain and an extra B30.2 (PRY/SPRY) domain at C-terminus. In addition, NLRC3a and NLRC3b were detected in all the examined tissues, with the highest expression levels in kidney and blood, respectively. After bacteria challenge, expression levels of turbot NLRC3 genes were strongly induced in intestine rather than in skin and gill, while NLRC3a had relatively higher expression level than that of NLRC3b. Taken together, NLRC3 genes found in this study were the first NLR members identified in turbot. The different expression signatures of NLRC3a and NLRC3b in mucosal tissues following two bacterial infections indicated they probably have important roles in early response to bacterial infection in the first line of host defense system. Highlights: NLRC3a and NLRC3b were identified in turbot. Turbot NLRC3a is homologous to their counterparts in other vertebrates. NLRC3b appears to be unique to teleost. NLRC3a and NLRC3b were ubiquitously expressed in turbot tissues. Expression of NLRC3a and NLRC3b were significantly induced after bacterial challenge.